2007
DOI: 10.1074/jbc.m703277200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the C-terminal Domain of a Potassium Channel from Streptomyces lividans (KcsA)

Abstract: KcsA, a potassium channel from Streptomyces lividans, is a good model for probing the general working mechanism of potassium channels. To date, the physiological activator of KcsA is still unknown, but in vitro studies showed that it could be opened by lowering the pH of the cytoplasmic compartment to 4. The C-terminal domain (CTD, residues 112-160) was proposed to be the modulator for this pH-responsive event. Here, we support this proposal by examining the pH profiles of: (a) thermal stability of KcsA with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…H4 in WSK3 is indeed protonated at pH Ϸ4.5 used in our studies, as confirmed by the chemical shifts of the imidazole H␦2 and H 1 (7.22 and 8.53 ppm, respectively). Similarly, the carboxy-terminal segment, when present, also modulates pore opening in response to decreasing pH, apparently by weakening the stability of the closed state at low pH (23). Thus, the cytoplasmic vestibule of the WSK3 pore, lacking the stability provided by a membrane environment, assumes a configuration that perhaps bears more resemblance to the state of transition to an open channel.…”
Section: Discussionmentioning
confidence: 99%
“…H4 in WSK3 is indeed protonated at pH Ϸ4.5 used in our studies, as confirmed by the chemical shifts of the imidazole H␦2 and H 1 (7.22 and 8.53 ppm, respectively). Similarly, the carboxy-terminal segment, when present, also modulates pore opening in response to decreasing pH, apparently by weakening the stability of the closed state at low pH (23). Thus, the cytoplasmic vestibule of the WSK3 pore, lacking the stability provided by a membrane environment, assumes a configuration that perhaps bears more resemblance to the state of transition to an open channel.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid cytosolic acidification that should follow CCCP addition might similarly affect ScMep2 activity. Nor can we exclude that pH variations might modulate a gating mechanism involving the C termini of Mep proteins, as shown for the potassium channel KcsA of Streptomyces lividans (51).…”
mentioning
confidence: 99%
“…EPR spectroscopy | K+ channel | X-ray crystallography M ost ion channels have structured cytoplasmic domains that influence their functional behavior [in regards to both gating (1-3) and permeation (4)], contribute to their structural stability (5,6) or allow them to directly interact with enzymes and other regulators (7). In the prokaryotic K þ channel KcsA, the 40-residue C-terminus forms a four-helix bundle that projects toward the cytoplasm (5).…”
mentioning
confidence: 99%
“…In the prokaryotic K þ channel KcsA, the 40-residue C-terminus forms a four-helix bundle that projects toward the cytoplasm (5). Removal of the C-terminus affects KcsA thermal stability, destabilizes the closed conformation (5,6) and enhances entry into the C-type inactivated state (8). Using chaperone-assisted crystallography, we recently determined the crystal structure of full-length (FL) KcsA in its closed conformation (1).…”
mentioning
confidence: 99%